Association of Musculoskeletal Disorders and Job Satisfaction Among Nurses Working in Hospitals of Lahore: Musculoskeletal Disorders and Job Satisfaction Among Nurses - Aslam, Intsam; Iqra, .; Baig, Tehreem; Fatima, Kanwal; Rafique, Hira; Noor, Shahmeer; Maqbool, Sania (Pakistan Journal of Health Sciences, 2023)
Musculoskeletal disorders are the most common work-related problems reported till today worldwide. This might be because nurses are engaged in activities that require continuous physical efforts and interaction with patients. Job satisfaction can be defined as how the employees feel about job and its attributes. Job satisfaction is one of the most important and common variables in work environment. Objective: To evaluate the association between musculoskeletal disorders and job satisfaction among nurses working in the hospitals of Lahore. Methods: This analytical cross-sectional study was conducted in Lahore. 194 subjects were enrolled. Nordic Musculoskeletal Questionnaire was used to assess musculoskeletal disorders. The Nursing Workplace Satisfaction Questionnaire was used to assess job satisfaction. The Data were analyzed using SPSS v20. Mean ± SD was calculated for numeric variables while chi square test was used find the association between musculoskeletal disorders and job satisfaction. Cut off value was used to make categories of satisfaction. Results: Chi- square test of independence showed no association among neck (0.475), shoulder (0.698), elbow (0.066), wrist/hand (0.857), upper back (0.076) and Low back pain (0.358), Knee pain (0.61), ankle/foot pain (0.329) and job satisfaction as p-value of each was > 0.05 but there was found to be slight positive association among hip/thigh pain and job satisfaction as P-value was 0.43 which is statistically significant. Conclusions: There was no association between musculoskeletal disorders and job satisfaction because there were some other factors that determined the job satisfaction. These factors may include low salary, work environment etc